Fenologia e produção de mudas de Portulaca oleracea subsp. sativa em clima tropical - Correa, Amanda Ribeiro (2017)
The species Portulaca oleracea subsp. sativa, known as purslane, has important nutritional and medicinal properties. The objective of this study was to describe the phenological cycle of the purslane according to the BBCH scale and to verify the duration of the main stages; to identify the interference of climatic conditions on the cycle and seed germination and to evaluate suitable methods for the seedlings production. For phenology and seed germination studies, purslane plants were grown in Cuiabá / MT, Brazil, from September 2015 to September 2016, with consecutive sowing every two months. Ten plants of the Golden variety (genotype 1) and a spontaneous occurrence (genotype 2) were considered. The phenology of purslane according to the BBCH scale and the duration of flowering stages, seed maturation and plant senescence were described. The base temperature and the thermal sum, in degrees-day for the change of main stages were determined by the least variability method. The mean number of capsules in the main branches of the two genotypes was estimated at 30 days and the data submitted to multivariate regression analysis. The seeds germination was evaluated at a temperature of 20-30 oC under a 12 - hour photoperiod. In the experiment on seedling production, three levels of shading (full sun, 30 and 50% shading), three container types (128, 200 and 288 cells) and five substrates (commercial, commercial + 5% mineral, commercial + 10% mineral, commercial + 10% earthworm humus and commercial + 20% earthworm humus). The design was completely randomized, in subsub-divided plots. The plant height, stem diameter, height-to-diameter ratio, leaf number, dry shoot and root mass, total chlorophyll content and Dickson quality index were evaluated. The phenological cycle of Portulaca oleracea subsp. sativa based on the BBCH scale involves seven main stages, subdivided into secondary and tertiary stages: germination (0); leaf development in the main branch (1); development of lateral branches (2); development of flower buds (5); flowering (6); seed maturity (8) and plant senescence (9). The genotype 1 shows a longer duration of the main phenological stages, in relation to genotype 2. The purslane has a shorter duration of the phenological phases in times of larger photoperiod and average temperatures around 29 oC. The lower basal temperatures determined by the thermal sum method from the emergence to the anthesis of the first flower of genotypes 1 and 2 are 10 and 15 oC. To reach seed maturity, genotypes 1 and 2 have a base temperature of 9 and 13 oC, respectively. The thermal requirements for anthesis of genotypes 1 and 2 are 457 and 253 degree-days, and 704 and 436 degree-days, on average, for seed maturity, respectively. The number of capsules of genotype 2 is higher in comparison to genotype 1 and positively correlated with the photoperiod. The percentage of seeds germination of the genotypes evaluated is between 79 and 100% and higher in times of lower precipitation, lower photoperiod and lower temperatures. Purslane seedlings produced in full sun conditions are of better quality, they present different responses in the different containers. The addition of earthworm humus to the commercial substrate favors the quality of seedlings. In conditions of greater light, the seedling shoots respond to higher doses of humus in the substrate.